ANALISIS LINGKUNGAN EKSTERNAL DAN INTERNAL TRAVELOKA DALAM UPAYA MENINGKATKAN DAYA SAING (Manajemen & Bisnis Jurnal, 2023)
Traveloka has effectively implemented a competitive strategy that has led it to become a successful company, especially in the field of travel and lifestyle. To understand the competitive strategy implemented, it is important to analyze Traveloka's internal and external environment. Internal analysis emphasizes the strengths of the company, while external analysis emphasizes the opportunities and threats faced by the company. The writing of this article uses the literature review method with Traveloka as the research subject. The results show that Traveloka's internal and external environments have successfully created a competitive strategy that differentiates it from competitors and appeals to the millennial market. Traveloka expands its reach to various tourist destinations, especially Indonesia, utilizes technology to offer better services and speed up the reservation process, unites various services such as flights, accommodation, and local transportation into one platform that can be easily accessed by customers, offers safe and healthy travel packages, and provides accurate and up-to-date information on health and safety measures at tourist destinations.